Acute severe idiopathic lymphoid interstitial pneumonia: A case report. Issue 30 (24th July 2020) - Lamkouan, Youssef; Dury, Sandra; Perotin, Jeanne Marie; Picot, Remi; Durlach, Anne; Passouant, Olivier; Sandu, Sebastian; Dewolf, Maxime; Dumazet, Antoine; Lebargy, François; Deslee, Gaëtan; Launois, Claire
Abstract: Rationale: Lymphoid interstitial pneumonia is a rare benign pulmonary lymphoproliferative disorder usually presenting with a sub-acute or chronic condition and frequently associated with autoimmune disorders, dysgammaglobulinemia, or infections. Patient concerns: A 74-year-old woman with no past medical history presented with acute dyspnea, nonproductive cough, hypoxemia (room air PaO2 : 48 mmHg) and bilateral alveolar infiltrates with pleural effusion. Antibiotics and diuretics treatments did not induce any improvement. No underlying condition including cardiac insufficiency, autoimmune diseases, immunodeficiency, or infections was found after an extensive evaluation. Bronchoalveolar lavage revealed a lymphocytosis (60%) with negative microbiological findings. High-dose intravenous corticosteroids induced a mild clinical improvement only, which led to perform a surgical lung biopsy revealing a lymphoid interstitial pneumonia with no sign of lymphoma or malignancies. Diagnoses: Acute severe idiopathic lymphoid interstitial pneumonia. Interventions: Ten days after the surgical lung biopsy, the patient experienced a dramatic worsening leading to invasive mechanical ventilation. Antibiotics and a new course of high-dose intravenous corticosteroids did not induce any improvement, leading to the use of rituximab which was associated with a dramatic clinical and radiological improvement allowing weaning from mechanical ventilation after 10 days. Outcomes: Despite the initial response to rituximab, the patient exhibited poor general state and subsequent progressive worsening of respiratory symptoms leading to consider symptomatic palliative treatments. The patient died 4 months after the diagnosis of lymphoid interstitial pneumonia. Lessons: Idiopathic lymphoid interstitial pneumonia may present as an acute severe respiratory insufficiency with a potential transient response to rituximab.